A influência da responsabilidade social corporativa na imagem da marca: um estudo em empresas brasileiras do setor de cosméticos - Fonseca, Márcio Ribeiro da (2014)
This study has as its theme the influence of Corporate Social Responsibility (CSR) in brand image and corporate reputation of Brazilian companies in the cosmetics industry. The focus of the research was to investigate the perception of college consumers belonging to classes A / B on the shares of CSR in two large Brazilian cosmetic companies. The objective was to compare the perceptions of consumers and point out the differences between the two companies. The development of this study occurred in two stages: the first stage involved a literature review, verifying theories and published research on corporate social responsibility, brand image and corporate reputation. The second stage involved collecting data through a survey of consumers in two large Brazilian cosmetic companies that publish social reports with GRI methodology. Next, the descriptive and multivariate statistical analysis from data collected through 200 questionnaires with consumers 19-24 years of the undergraduate students in Communication with an emphasis in Advertising at the School of Advertising and was performed marketing - ESPM. The results showed that CSR has a positive influence on brand image, but this influence was demonstrated only significant for one of the brands studied, moderate to second. Among the contributions of this work are to review the literature on the subject, notes the influence of variables subconstrutos and CSR on brand image and corporate reputation and consumer perception of the differences for each of the brands studied, as well as recommendations for future studies.